Inventing Atlantic Canada : Regionalism and the Maritime Reaction to Newfoundland's Entry into Canadian Confederation - Slumkoski, Corey, 1972- (Book collections on Project MUSE., 2011)
Inventing Atlantic Canada is the first book to analyse the reaction of the Maritime provinces to Newfoundland's entry into Confederation.